Concentration of NR filed latex using tubular cross flow ultrafiltration system - Veerasamy Devaraj; Aziz Y; Nambiar J; Sulaiman N M (Journal of Rubber Research, 2003)
This study presents an alternative method of concentrating field latex (FL) that produced latex concentrate and a clear serum as a by-product. The serum obtained could be utilised for the extraction of useful biochemicals; and as it was not contaminated by sulphuric acid, value-added products from waste could also be obtained. A tubular cross flow ultrafiltration system, one of the pressure-driven membrane separation techniques, was used to examine the concentration process of FL. A suitable preservation system to increase the stability of latex to withstand mechanical shear stresses during ultrafiltration was investigated. Fouling of membrane could be reduced by a cleaning-in-place (CIP) technique and also by adopting suitable cleaning protocols. Results showed that FL with a suitable composite preservation system could be concentrated from 30;DRC to 46;DRC, by applying CIP with transmembrane pressure of 2.5 bar.
Keywords: Field latex; Latex concentrates; Latex-stability; Membrane separation; Serum; Transmembrane pressure; Ultrafiltration